The Influence of Pop Up Book Media on the Mastery of Mufradat for Grade IV Students Mis Al-Mubarakah Mohiyolo - Daud, Siska; Hairuddin; M. Mooduto, Dzulkifli (Yayasan Daarul Qimmah Gorontalo, 2024)
This study aims to determine the influence of the use of Pop Up Book media in learning Arabic in grade IV, especially in students' mastery of mufradat. The research was conducted at MIS Al-Mubarakah Mohiyolo by involving grade IV students as research subjects. The research method used is an experiment with a quantitative approach with a quasi-experimental design, which can compare the conditions before and after the treatment. Data was collected through pre-test and post-test tests to measure students' mastery of mufrodat. The results of the data analysis showed that there was a significant influence of the use of Pop Up Book media on students' mastery of mufrodat. This can be seen from the results of the hypothesis test using the Mann-Whitney test obtained a significance value (2-tiled) < 0.05, so there is a significant influence on the experimental class. So it can be concluded that the hypothesis is accepted.